Characterization of gas-liquid flows in rectangular bubble columns using conductivity probes - Buwa, Vivek V.; Ranade, Vivek V. (Chemical Engineering Communications, 2005)
Unsteady gas-liquid flows in bubble columns are comprised of various flow processes occurring with varying length and time scales and govern mixing and transport processes. In the present work, we have characterized dynamic and time-averaged properties of gas-liquid flows in rectangular bubble columns using conductivity probes. The development of a single-tip conductivity probe, data processing methodology, and photographic validation procedure is discussed in detail. The effect of superficial gas velocity and aerated liquid height-to-width ( H/W) ratio on voidage fluctuations and time-averaged gas holdup was investigated. The experimental data presented here can help in understanding the dynamics of various flow processes and validating computational fluid dynamics based models.
Keywords: Bubble column; gas holdup; gas-liquid flows; voidage fluctuations

Comparison of flow structures in spacer-filled flat and annular channels - Ranade, Vivek V.; Kumar, Anil (Desalination, 2006)
Spacers are designed to create directional changes in the flow through membrane modules. Such secondary flow structures reduce concentration polarization and membrane fouling. Obviously, type of the spacer used in membrane modules strongly influences the resulting flow and therefore performance of the module. In this work, we have modeled detailed fluid dynamics of spacer filled channels by using the `unit cell' approach. The validated computational fluid dynamics (CFD) model was used to evaluate performance of certain spacer shapes and compare the resulting fluid dynamics in flat and curved channels. The simulations show that fluid flow behavior in a spacer-filled flat and a spiral channel was not significantly different. This means that pressure drops and mass transfer coefficients measured in flat channels may provide adequate guidelines, which would also be valid for spiral-wound modules. The results presented in this work will have significant implications for identifying improved spacers with higher propensities to reduce fouling in membrane modules.
International Congress on Membranes and Membrane Processes, Seoul, SOUTH KOREA, AUG 21-26, 2005
Keywords: annular channel; CFD; flat channel; membrane spacers

CFD modeling of rotary cement kilns - Mujumdar, Kaustubh S.; Ranade, Vivek V. (Asia-Pacific Journal of Chemical Engineering, 2008)
Rotary cement kilns are widely used to convert calcineous raw meal into cement clinker, and are key components in the cement industry. In this article, we report a comprehensive computational fluid dynamics (CFD)-based model to capture key transport processes in rotary cement kilns. Separate but coupled computational models were developed for the bed and the freeboard regions of the rotary kiln. The complex swirling airflow produced by kiln burners, coal combustion, gas-phase combustion of volatile matter and radiative heat transfer in the freeboard region were modeled. The clinkerization reactions in the bed region were modeled assuming solids as pseudo fluids. Coating formation in cement kilns (for both bed and freeboard regions) was considered. Appropriate source and sink terms were developed to model transfer of CO(2) from the bed to the freeboard region due to calcination reaction in the bed region. The developed bed and freeboard models were coupled by mass and energy communication through common interface. These coupled computational models were able to quite satisfactorily predict the available data from industrial kilns and previously published results. The computational models were also able to capture the intricacies of the burning zones of rotary cement kilns for changing burner-operational parameters like axial to swirl ratio and oxygen enrichment. The developed approach, computational models and simulation results will not only help in developing better understanding of cement kilns but also provide quantitative information about influence of burner design and other design parameters on kiln performance. (C) 2008 Curtin University of Technology and John Wiley & Sons, Ltd.
Keywords: burner; CFD; coal combustion; rotary cement kiln

CFD simulation of stirred tanks: comparison of turbulence models (Part II: axial flow impellers, multiple impellers and multiphase dispersions) - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
In the first part of the review, published literature regarding the CFD modelling of single-phase turbulent flow in stirred tank reactors with radial flow impellers was critically analysed. A brief overview of different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model and large eddy simulation) as well as impeller baffle interaction models has been presented in the previous part. This part is concerned with the review of literature regarding CFD simulation of axial flow impellers. Comprehensive simulations have been carried out using various turbulence models and the model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. The strengths and weaknesses of various turbulence models for axial flow impellers is presented. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-e model as well as Reynolds stress model. Literature efforts on multiple impeller systems and multiphase systems have been discussed in a separate section. Based on these results, suggestions have been made for the future work in this area.
Keywords: axial flow impellers; CFD; impeller models; stirred vessel; turbulence models

CFD simulation of stirred tanks: comparison of turbulence models. part I: radial flow impellers - Joshi, Jyeshtharaj B.; Nere, Nandkishor K.; Rane, Chinmay V.; Murthy, B. N.; Mathpati, Channamallikarjun S.; Patwardhan, Ashwin W.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2011)
A critical review of the published literature regarding the computational fluid dynamics (CFD) modelling of single-phase turbulent flow in stirred tank reactors is presented. In this part of review, CFD simulations of radial flow impellers (mainly disc turbine (DT)) in a fully baffled vessel operating in a turbulent regime have been presented. Simulated results obtained with different impeller modelling approaches (impeller boundary condition, multiple reference frame, computational snap shot and the sliding mesh approaches) and different turbulence models (standard k-epsilon model, RNG k-epsilon model, the Reynolds stress model (RSM) and large eddy simulation) have been compared with the in-house laser Doppler anemometry (LDA) experimental data. In addition, recently proposed modifications to the standard k-epsilon models were also evaluated. The model predictions (of all the mean velocities, turbulent kinetic energy and its dissipation rate) have been compared with the experimental measurements at various locations in the tank. A discussion is presented to highlight strengths and weaknesses of currently used CFD models. A preliminary analysis of sensitivity of modelling assumptions in the k-epsilon models and RSM has been carried out using LES database. The quantitative comparison of exact and modelled turbulence production, transport and dissipation terms has highlighted the reasons behind the partial success of various modifications of standard k-epsilon model as well as RSM. The volume integral of predicted energy dissipation rate is compared with the energy input rate. Based on these results, suggestions have been made for the future work in this area.
Keywords: CFD; impeller models; k-epsilon models; LES; radial flow impellers; RSM; stirred vessel

Computational fluid dynamics modelling of solid suspension in stirred tanks - Sardeshpande, Madhavi V.; Ranade, Vivek V. (Current Science, 2012)
Solid suspension and mixing are crucial in many important processes, including multiphase catalytic reactions, crystallization, precipitation, etc. In recent years, various efforts have been made to numerically simulate solid-liquid flows in stirred vessels using computational fluid dynamics (CFD). In this article, we present a brief account of our group's efforts at developing and using CFD models for simulating solid suspension in stirred tanks. Computational models were developed and evaluated by comparing model predictions with our data as well as published experimental data. A variety of experimental techniques ranging from torque and wall pressure fluctuations to ultrasound velocity profiler were used. Efforts were made to develop appropriate sub-models for capturing influence of the prevailing turbulence and solid volume fraction on effective inter-phase coupling terms. A hysteresis in variation of the height of the cloud of suspended solid with impeller rotational speed was observed. The hysteresis, besides having applications in realizing better suspension at lower effective power consumption, also offers an attractive evaluation test for CFD models. A new way to carry out dynamic settling of solid cloud by sudden impeller stoppage has been developed. The approach, models and results presented here will be useful for extending applications of CFD models for simulating industrial stirred slurry reactors as well as further research in the field.
Keywords: computational fluid dynamics; hysteresis; solid suspension; stirred tanks

Crystallization: key thermodynamic, kinetic and hydrodynamic aspects - Vedantam, Sreepriya; Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)
Crystallization is extensively used in different industrial applications, including the production of a wide range of materials such as fertilizers, detergents, food and pharmaceutical products, as well as in the mineral processing industries and treatment of waste effluents. In spite of the wide-spread use of crystallization, a clear understanding of the thermodynamic, kinetic and hydrodynamic aspects of the design methodologies are not yet well established. More often than not crystallization is still considered an art especially in fine-chemicals, pharmaceuticals and life-sciences sector. It is essential to understand and relate key thermodynamic, kinetic and hydrodynamic aspects to crystallizer performance, not just in terms of yield but also in terms of product quality (characterized by particle size distribution, morphology, polymorphism and the amount of strain as well as the uptake of solvent or impurities in the crystal lattice). This paper attempts to do that by critically reviewing published experimental and modelling studies on establishing and enhancing state-of-the-art thermodynamic, kinetic and hydrodynamic aspects of crystallization. Efforts are made to discuss and raise points for emerging modelling tools needed for a flexible design and operation of crystallizers and crystallization processes that are needed to meet the ever increasing demand on precise product specifications. Focus is on bringing out the trends which can be used as perspectives for future studies in this field.
Keywords: CFD; Crystallization; growth; Nucleation; polymorphism; supersaturation

Crystal shape evolution using polyhedral population balance - Shaikh, Latif J.; Ranade, Vivek V.; Pandit, Aniruddha B. (Industrial & Engineering Chemistry Research, 2014)
Research on crystal morphology covers shape evolution of single crystal and evolution of the size and shape distribution of populations of crystals. The population balance models have been used for the single or multiple dimensions for predicting the evolution of crystal size distributions (CSDs). More often than not these models do not consider the change in solute concentration due to disappearance/appearance of the crystal faces and therefore compromise rigorous mass balance. The present work focuses on the methodology for the morphological evolution of crystal shape using a polyhedral population balance model. This methodology is based on the morphodrome which illustrates the shapes of crystals at various operating conditions. gPROMS software (PSE, UK) along with Microsoft Excel is used to devise the framework for predicting the crystal shape evolution. The developed approach and models can be implemented for various crystallization systems and will be useful for simulating crystal shape evolutions.

CRE for magic(modular, agile, intensified & continuous) processes - Ranade, Vivek V.; Sharma, Mrityunjay K.; Kulkarni, Amol A. (Chemical Engineering Journal, 2015)
Fine and specialty chemical industry caters to several key applications required for maintaining and enhancing quality of life. Most of these fine and specialty chemicals are still manufactured in stirred tank reactors operated in batch or semi-batch modes. A paradigm shift is necessary to transform these into new age, efficient and continuous processes and plants. In this paper, recent attempts of our group on developing MAGIC (modular, agile, intensified and continuous) devices, processes and plants for fine and specialty chemicals industry are discussed. The focus is on key chemical reaction engineering aspects of developing MAGIC processes. An attempt is made to evolve guidelines for designing MAGIC devices and reactors. The discussion will be useful to researchers as well as to industry practitioners. (C) 2014 Elsevier B.V. All rights reserved.
23rd International Symposium on Chemical Reaction Engineering (ISCRE), Bangkok, THAILAND, SEP 07-10, 2014
Keywords: Agile; Continuous; CRE; Intensified; Modular

Chord length distribution to particle size distribution - Pandit, Ajinkya V.; Ranade, Vivek V. (AICHE Journal, 2016)
A simple model is presented to extract the particle size distribution (PSD) from the chord length distribution measured using a focused beam reflectance measurement probe. The model can be implemented using simple spread sheeting tools and does not require the description of additional parameters as opposed to previous models. The model was validated for two systems consisting of spherical ceramic beads by comparing model predicted PSD against the PSD obtained through image analysis (IA). Then, the model was evaluated by considering various systems consisting of irregularly shaped particles (sand/zinc dust/plasma alumina). Model predictions accurately predicted the mean but over-predicted the variance of the PSD in comparison with the PSD obtained from IA. However, overall, a reasonable agreement was observed. Finally, the model was shown to be accurate in predicting PSD in comparison with the measured PSD for systems of practical relevance such as for paracetamol and p-aminophenol crystals. (c) 2016 American Institute of Chemical Engineers AIChE J, 62: 4215-4228, 2016

CFD modelling of almond drying in a tray dryer - Chilka, Amarvir G.; Ranade, Vivek V. (Canadian Journal of Chemical Engineering, 2019)
Drying is important in many food processing applications, and particularly so in the dry fruits industry. This work is focused on developing computational models for simulating the drying of almonds in a tray dryer. It is important to quantitatively understand heat and mass transfer within and around a single almond particle as well as the particle-particle interactions and their implications for dryer design. In this work, we have developed a systematic CFD modelling framework for modelling almond drying in a tray dryer. A single tray filled with almonds (similar to 2 kg) were dried at three set temperatures viz., 55, 65, and 75 degrees C. Air relative humidity at the inlet and outlet locations, and the weight of almonds were measured during drying for each experiment. An additional set of experiments were conducted in which almonds were filled only in the half section of the tray, keeping the other half empty. The same amount of almonds were used, to have multiple layers of almonds in the tray, and the set temperature for the experiment was 75 degrees C. Flow, heat, and mass transfer in the tray dryer were simulated using commercial CFD software Ansys Fluent. The validated computational model was used to simulate various cases including larger and more trays. The developed approach and models will be useful to select the appropriate dryer configuration and optimize its design. The developed models will also be useful to identify suitable operation conditions for the drying of almonds as well as other food products.
Keywords: Almonds; CFD; Drying; scale-up; tray dryer

Continuous hydrogenation of cinnamaldehyde: gas-liquid-liquid-solid helical coil reactor - Khan, Muzammil Y.; Joshi, Sunil S.; Ranade, Vivek V. (Industrial & Engineering Chemistry Research, 2023)
The advantages and challenges of using the gas-liquid-liquid-solid(GLLS) hydrogenation system are discussed in this work using the caseof selective hydrogenation of cinnamaldehyde to cinnamyl alcohol (animportant ingredient in the perfume and flavoring industry). The fourphases in this system include gas (hydrogen)-liquid (organic, reactant+ solvent)-liquid (aqueous KOH)-solid (5% Pt/C catalyst). The additionof second liquid phase, i.e., aqueous KOH significantly increasesselectivity toward cinnamyl alcohol compared to the conventional three-phasehydrogenation. The four-phase GLLS reactions were carried out andoptimized in a continuous helical coil reactor. The role of key aspectssuch as gas solubility, kinetics, flow hydrodynamics, axial dispersion,and mass transfer on the performance of a continuous GLLS reactoris presented and discussed in this work. The presented results anddiscussion will be useful for addressing conflicting demands likelong residence time, low axial dispersion, and high mass transfer.The experimental studies and results of the developed mathematicalmodel indicate that the continuous GLLS helical coil reactor outperformsthe batch operation. The production rates (kg day(-1)) of cinnamyl alcohol achieved in continuous operation were at leastdouble in comparison to batch operation, with 32% less consumptionof precious catalyst (per kg of product). The presented results will open up new opportunities for enhancing selectivity and overall performanceof hydrogenations via introducing a second immiscible liquid phaseand designing continuous tubular reactors for the same.